Knowledge of modern contraceptives among undergraduate students of College of Health Sciences of Usmanu Danfodiyo University Sokoto, Nigeria - Muhammad, Ahmad Maryam; Habibullah, Adamu; Muhammad, Ismail Ahmad; Muhammed, Auwalu; Nakakana, Usman Nasir; Muhammad, Hindatu Tukur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Many undergraduate students in Nigerian Universities are at increased risk of sexually transmitted infections, unwanted pregnancies with resultant illegal abortions. The aim of this study is to assess the undergraduate students’ knowledge of contraceptives. Understanding the knowledge of contraception among students is essential in tackling unwanted pregnancies among youths. Methods: The researchers use cross-sectional survey, a quantitative approach to the stated objective. About fifty five (55) female students aged 18 to 21 years were enrolled in the study using purposive sampling technique. The instrument for data collection was a structured questionnaire. The fifty five (55) completed questionnaires were retrieved and data analyzed using SPSS version 20. Results: The result showed that current overall contraception knowledge was low, while general contraceptive knowledge is high among the student. However, the knowledge of both short-term and long term acting contraceptive methods were very low as reported by the respondents. Conclusions: This study has implication for health education especially on the use of modern contraceptives. Thus, recommendations were highlighted to improve students’ knowledge of the various contraceptive methods.